Chemical vapor deposition growth and photodetector performance of lead-free all-inorganic crystalline Cs3Sb2X9 (X = I, Br) perovskite thin films. Issue 14 (20th March 2023) - Shil, Sujit Kumer; Wang, Fei; Egbo, Kingsley O.; Wang, Ying; Kwok, Cheuk Kai Gary; Tsang, Sai-W.; Ho, Johnny C.; Yu, Kin Man
Abstract : Lead-free inorganic halide perovskites are non toxic and stable with unique properties making them suitable for many optoelectronic devices. We fabricated photodetectors with their thin films which demonstrated excellent photodetection performance. Abstract : Lead-based organic or inorganic halide perovskites (ABX3, A = organic or inorganic cation, B = lead cation, and X = Cl, Br, I) are well-known for their excellent properties and are technologically suitable for many optoelectronic devices. However, the stability of organic hybrid compounds and the toxicity of lead (Pb) inhibit the development and commercialization of these devices. Consequently, Pb-free, all-inorganic halide perovskites are now the subject of the recent research interest. In this work, we report on the synthesis and properties of Pb-free all-inorganic Cs3 Sb2 X9 (X = I, Br) perovskite thin films by a two-step CVD approach. The obtained Cs3 Sb2 I9 and Cs3 Sb2 Br9 thin films show good crystallinity and exhibit high exciton binding energies with large Stokes shifts of ∼570 and ∼630 meV, respectively. Refractive indices of 2.0 and 1.7 were obtained for Cs3 Sb2 I9 and Cs3 Sb2 Br9 thin films at their respective emission energies. The optical bandgaps were confirmed to be 2.2 and 2.85 eV for Cs3 Sb2 I9 and Cs3 Sb2 Br9 thin films. Photoconductive devices fabricated using these thin films exhibit commendable performance with responsivity of up to 54.5 and 3.6 mA W −1 and high detectivity reaching 4.3 × 10 10 and 1.6 × 10 10 Jones for Cs3 Sb2 I9 and Cs3 Sb2 Br9, respectively. Moreover, a stable photoswitching property with fast rise and decay times of 50 ms and 30 ms for Cs3 Sb2 I9 and 108 ms and 56.2 ms for Cs3 Sb2 Br9 film photodetectors was observed. The thin films exhibit excellent long-term stability even when stored without encapsulation in ambient air. The properties of these crystalline Cs3 Sb2 X9 perovskite films and their photodetector performance suggest that they can be promising candidates for a wide range of optoelectronic devices.